The interfacial structure of InP(100) in contact with HCl and H2SO4 studied by reflection anisotropy spectroscopy. Issue 50 (15th November 2022) - Löw, Mario; Guidat, Margot; Kim, Jongmin; May, Matthias M.
Abstract : Electrochemical reflection anisotropy spectroscopy reveals the reversible re-structuring of InP surfaces in contact with low-concentration electrolytes upon applied potentials, while higher concentrations induce non-reversibility. Abstract : Indium phosphide and derived compound semiconductors are materials often involved in high-efficiency solar water splitting due to their versatile opto-electronic properties. Surface corrosion, however, typically deteriorates the performance of photoelectrochemical solar cells based on this material class. It has been reported that (photo)electrochemical surface functionalisation protects the surface by combining etching and controlled corrosion. Nevertheless, the overall involved process is not fully understood. Therefore, access to the electrochemical interface structure under operando conditions is crucial for a more detailed understanding. One approach for gaining structural insight is the use of operando reflection anisotropy spectroscopy. This technique allows the time-resolved investigation of the interfacial structure while applying potentials in the electrolyte. In this study, p-doped InP(100) surfaces are cycled between anodic and cathodic potentials in two different electrolytes, hydrochloric acid and sulphuric acid. For low, 10 mM electrolyte concentrations, we observe a reversible processes related to the reduction of a surface oxide phase in the cathodic potential range which is reformed near open-circuit potentials. Higher concentrations of 0.5 N, however, already lead to initial surface corrosion.